Laporan Kasus Hepatopulmonary Syndrome (HPS) pada Pasien Sirosis Hepatis dengan Penyulit Melena Akut dan Orthodeoxia - Yogi Haditya; I Ketut Mariadi (MEDICINUS, 2026)
Hepatopulmonary syndrome (HPS) is a complication that frequently occurs in patients with end-stage liver disease. It is characterized by a triad of abnormal arterial oxygenation, intrapulmonary vascular dilatations (IPVD), and chronic liverdisease. A 48-year-old man presented with complaints of shortness of breath for about 3 months, which improved when lying down but worsened when sitting or standing. The patient also reported blackish stool since one day prior to admission and had a history of liver cirrhosis since 2020. Vital signs were normal except for peripheral oxygen saturation, which was 86% when lying down and 79% when sitting. Physical examination revealed anemic palpebra, clubbing finger on hands and foots. Laboratory results revealed anemia, with an increased alveolar-arterial (A-a) gradient of 64.7 mmHg on blood gas analysis. A transthoracic contrast echocardiography (TTCE) or “buble study” was performed and the result show more than 20 microbubles in the left chambers of the heart after 5 cardiac cycles, indicating an intrapulmonary shunt caused by IPVD. These findings confirmed the diagnosis of HPS. Management of HPS is supportive, as there is no specific medical therapy available other than liver transplantation.